On the intermediality of the Lesya Ukrainka essay "Loud strings" - Kalenichenko, Olha (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
Intermediate approach allows to comprehend the text of Lesya Ukrainka's essay "Loud strings" as an original experiment. The novelty of the research lies in considering the composition of the essay as a sonata form (sonata allegro). As in the sonata form, "Loud Strings" can be divided into three parts – exposition, development and reprise. Moreover, the exposition is preceded by an introduction that allows the writer to reveal the main features of the portrait and character of the main heroin, Nastya Gritsenko. In the exposition of the essay, as in the sonata form, four parts are clearly presented: the "main", associated with music, as indicated by the title of the work, and the busts of Beethoven and Chopin in Nastya's house, the "connecting" in which the name of Paul's beloved appears, brother Nastya, "side", which is based on the motive of the letter received by the girl from Bogdan, and "final", in which Paul's love for Olesya is revealed.As in the development of the sonata form, a short introductory section can be distinguished in the essay, the development itself and the background. Moreover, in the first sections, the motive of the letter of the "side" party dominates, either forcing Nastya to listen to the voice of her love for Bogdan, or evoking memories of meetings with him from the very beginning. In addition, in the development Lesya Ukrainka actively refers to allusions and reminiscences, inviting the reader to "recall" a wide range of works of world classical literature and music. Such intertext allows the writer to reveal Nastya's rich spiritual world.In the reprise, the leading role is played by the "connecting" and "main" parts, based respectively on the performance of Olesya's "Desires" by Chopin and Nastya – the third movement of Beethoven's sonata No. 17, since the "side" part has completely exhausted itself in development. To reveal the complex range of feelings Nastya Lesya Ukrainka turns to musical ecphrasis. The last lines of the essay can be interpreted both as the complete collapse of the heroine's hopes, and as the catharsis she is experiencing. At the same time, the happy Paul is not able to help his sister. Obviously, the philosophical conclusion of Lesya Ukrainka herself emerges through the "final" game – life is filled with dialectical contradictions.In general, the essay can be viewed as a neo-mythological text, in which the writer skillfully plays with “various traditions” (Z. Mints).